A spatial multi-scale integer coding method and its application to three-dimensional model organization. Issue 10 (2nd October 2020) - Lai, Guangling; Tong, Xiaochong; Zhang, Yongsheng; Ding, Lu; Sui, Yinling; Lei, Yi; Zhang, Yong
ABSTRACT: With the rapid development of digital earth, smart city, and digital twin technology, the demands of three-dimensional model data's application is getting higher and higher. These data tend to be multi-objectification, multi-type, multi-scale, complex spatial relationship, and large amount, which brings great challenges to the efficient organization of them. This paper mainly studies the organization of three-dimensional model data, and the main contributions are as follows: 1) A integer coding method of three dimensional multi-scale grid is proposed, which can reduce the four-dimensional (spatial dimension and scale dimension) space into one-dimensional, and has better space and scale clustering characteristics by comparing with various types of grid coding. 2) The binary algebra calculation method is proposed to realize the basic spatial relationship calculation of three-dimensional grid, which has higher spatial relationship computing ability than 3D-Geohash method; 3) The multi-scale integer coding method is applied to the data organization of three-dimensional city model, and the experiment results show that: it is more efficient and stable than the three-dimensional R-tree index and Geohash coding method in the establishment of index and the query of three dimensional space.